Himalayan “S-type” granite generated from I-type sources - Huixia Ding; Zeming Zhang; Matthew J. Kohn (Proceedings of the National Academy of Sciences, 2025)
Partial melting of metasedimentary rocks is generally accepted as the source of peraluminous Himalayan leucogranites—they are commonly considered as pure “S-type” (sedimentary source) granites. Here, a uniquely comprehensive geochronological and geochemical dataset shows that partial melting of metaigneous rocks in the eastern Himalaya produced peraluminous leucogranites—these supposed S-type leucogranites have I-type (igneous) sources. Inherited magmatic zircons from leucogranites and metaigneous rocks have indistinguishable ages, trace element compositions, and Hf isotope compositions, distinct from zircons in metasedimentary rocks. Experimentally, partial melting of metagranitic rocks rather than metapelites predicts alkali major element chemistry of these leucogranites better. High δ 18 O, high 87 Sr/ 86 Sr, and low ε Nd (t) for Himalayan leucogranites have been used to argue for a metasedimentary rock source, but overlapping values occur in metaigneous rocks. Although sediment-sourced leucogranites also occur, igneous-sourced leucogranites are likely common in large hot orogens. A survey of leucogranite geochemistry across the Himalaya suggests that ~20% might be I-type, with no apparent spatial or temporal bias. I-type leucogranites appear to be rare-metal poor, however. Unlike prior assertions that I-type granites represent juvenile additions to orogens, metaigneous-sourced Himalayan granites more likely represent crustal reworking.